The Price of Progressive Politics : the Welfare Rights Movement in an Era of Colorblind Racism. - Ernst, Rose (NYU Press, 2010)
Social justice activists in the United States face an increasingly difficult task: how do they fight policies based on damaging images of race, class and gender identities in an era of "colorblind" racism? Through the voices of women activists in the welfare rights movement across the United States, The Price of Progressive Politics exposes the contemporary reality of welfare rights politics, revealing how the language of colorblind racism undermines this multiracial movement. Rose Ernst argues that although many activists are well-meaning and truly committed, they nonetheless find themselves.